Planejamento da produção na indústria de embalagens em polpa moldada - Martínez, Karim Yaneth Pérez (2013)
This research deals with the production planning and scheduling problem in the molded pulp packing industry, studying particularly a plant of molded pulp packages for eggs. The production process can be subdivided into two processes: molding process and printing process. The main challenge for production planning activities is on the molding process, where products are produced through tooling that have several molds. These tooling are called "Molding Patterns" or " Conformation Patterns". Each one of the molding patterns can contain one, two, until three kind of molds, allowing to produce several products simultaneously. Producing several products at the time can generate large inventory for low demand products and also null inventory for high demand products. Thus, different inventory levels are defined for each product based on their demand behavior, in order to control inventory quantities. In this way, decisions related to the production planning and scheduling in this production process involve deciding which molding patterns should used, how much time they should be used, and how they should be sequenced. All these should be make taking into account a parallel machine system and sequenced-dependent setups time and costs, in order to minimize inventory and setups costs, as well as penalties associated to inventory out of the specified inventory levels of each product. To represent this problem we proposed two formulations: the first one based on the Capacitated Lot Sizing and Scheduling Problem (CLSP), and the second one based on the General Lot Sizing and Scheduling Problem (GLSP). The results from the models were compared in a set of real word instances of a plant, in order to check the adequacy to represent the decisions involved in the studied production process, as well as the main differences between their production plans and performance of the models. The proposed formulations were also adapted for a particular instance, in order to compare their productions plans against the production plan implement by the studied plant. Results show that the proposed models represent rightly decisions involved in the production planning and scheduling in the molded pulp. Furthermore, the solutions obtained by the proposed models represent production plans with costs significantly lower than the schedule implemented by a real plant in this kind of industry.